2019
DOI: 10.1177/0333102419854082
|View full text |Cite
|
Sign up to set email alerts
|

Long-term safety and tolerability of erenumab: Three-plus year results from a five-year open-label extension study in episodic migraine

Abstract: Background Previously published three-month placebo-controlled and one-year open-label clinical trial data have provided information on the efficacy and safety of erenumab. Methods Interim analysis was undertaken from an ongoing five-year open-label treatment phase after all patients completed three years in the open-label treatment phase or discontinued the study. Adult patients with episodic migraine enrolled in the open-label treatment phase initially received 70 mg erenumab monthly. A protocol amendment in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
101
1
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(121 citation statements)
references
References 24 publications
6
101
1
13
Order By: Relevance
“…69,70 Patients receiving 70 mg every 4 weeks had significant reduction in MDD at week 64, with 65% of patients achieving ≥50% reduction and 26% achieving 100% reduction. Interim analysis of a 5-year open label extension study of erenumab provides further efficacy and safety information.…”
Section: Cgrp Monoclonal Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…69,70 Patients receiving 70 mg every 4 weeks had significant reduction in MDD at week 64, with 65% of patients achieving ≥50% reduction and 26% achieving 100% reduction. Interim analysis of a 5-year open label extension study of erenumab provides further efficacy and safety information.…”
Section: Cgrp Monoclonal Antibodiesmentioning
confidence: 99%
“…Interim analysis of a 5-year open label extension study of erenumab provides further efficacy and safety information. 69 Erenumab 140 mg administration has also been studied in patients with stable angina and was not shown to adversely affect treadmill exercise time. 68 A protocol amendment increased to dose to 140 mg every 4 weeks to assess safety at the higher dose, with a median exposure to the medication of 3.2 years.…”
Section: Cgrp Monoclonal Antibodiesmentioning
confidence: 99%
“…Also, studies on the use of mindfulness and ACT in migraine have demonstrated improvement in patients’ ability to tolerate pain, reduce the use of symptomatic medications and to modulate specific characteristics of the migraine personality (rigidity, low acceptance, and low resilience) . Recently, the calcitonin gene‐related peptide monoclonal antibodies (MAbs), innovative and specific, but costly pharmacological therapies have been introduced and have shown benefit in the management of both episodic and chronic migraine . Real‐world experiences with some of these drugs are just being published …”
Section: Monthly Migraine Days and Treatment Doses In Each Treatment mentioning
confidence: 99%
“…Recently, the calcitonin gene‐related peptide monoclonal antibodies (MAbs), innovative and specific, but costly pharmacological therapies have been introduced and have shown benefit in the management of both episodic and chronic migraine . Real‐world experiences with some of these drugs are just being published …”
Section: Monthly Migraine Days and Treatment Doses In Each Treatment mentioning
confidence: 99%
“…As noted in the previous review, 1 year of open label data on erenumab was published for safety and efficacy in EM prevention . At the AHS meeting, the investigators provided an interim analysis for what is planned as a 5‐year OLE for EM prevention in which 61.3% (235 patients) completed ≥3 years in the trial …”
Section: Migraine Monoclonal Antibodiesmentioning
confidence: 99%